Are there changes in postural regulation across the lifespan?. (December 2013) - Schwesig, René; Fischer, David; Kluttig, Alexander
Abstract The purpose was to obtain parameters of postural regulation (n = 1724) of asymptomatic subjects (6–97 years). The maximum postural stability and capacity of postural subsystems were calculated for the age ranges from 34 to 35 years (men) and from 38 to 44 years (women). A significant decline in postural performance was observed in the 40s (men) and 50s (women). Data can be used in the evaluation of dizziness and balance disorders in people of all ages.